cFLIP overexpression in T cells in thymoma-associated myasthenia gravis - Belharazem, Djeda; Schalke, Berthold; Gold, Ralf; Nix, Wilfred; Vitacolonna, Mario; Hohenberger, Peter; Rößner, Eric; Schulze, Torsten; Saruhan-Direskeneli, Güher; Yilmaz, Vuslat; Ott, German; Ströbel, Philipp; et al. (Annals of Clinical and Translational Neurology, 2015)
Objective The capacity of thymomas to generate mature CD4+ effector T cells from immature precursors inside the tumor and export them to the blood is associated with thymoma-associated myasthenia gravis (TAMG). Why TAMG(+) thymomas generate and export more mature CD4+ T cells than MG(−) thymomas is unknown. Methods Unfixed thymoma tissue, thymocytes derived thereof, peripheral blood mononuclear cells (PBMCs), T-cell subsets and B cells were analysed using qRT-PCR and western blotting. Survival of PBMCs was measured by MTT assay. FAS-mediated apoptosis in PBMCs was quantified by flow cytometry. NF-κB in PBMCs was inhibited by the NF-κB-Inhibitor, EF24 prior to FAS-Ligand (FASLG) treatment for apoptosis induction. Results Expression levels of the apoptosis inhibitor cellular FLICE-like inhibitory protein (c-FLIP) in blood T cells and intratumorous thymocytes were higher in TAMG(+) than in MG(−) thymomas and non-neoplastic thymic remnants. Thymocytes and PBMCs of TAMG patients showed nuclear NF-κB accumulation and apoptosis resistance to FASLG stimulation that was sensitive to NF-κB blockade. Thymoma removal reduced cFLIP expression in PBMCs. Interpretation We conclude that thymomas induce cFLIP overexpression in thymocytes and their progeny, blood T cells. We suggest that the stronger cFLIP overexpression in TAMG(+) compared to MG(−) thymomas allows for the more efficient generation of mature CD4+ T cells in TAMG(+) thymomas. cFLIP overexpression in thymocytes and exported CD4+ T cells of patients with TAMG might contribute to the pathogenesis of TAMG by impairing central and peripheral T-cell tolerance.